T/A Polymorphism of the FTO Gene and Adiposity in Young Mongolian Men - Bondareva, Elvira; Gundegmaa, Lkhagvasuren; Galsanjav, Otgon (Central Asian Journal of Medical Sciences, 2019)
Objectives: The purpose of the paper was to determine the association between T/A polymorphism of the FTO gene and fat accumulation and localization in young urban ethnic Mongolian males. Methods: The anthropogenetic study was conducted 247 ethnic Mongolian males in Ulaanbaatar, Mongolia from 18 to 24 years of age, whose parents were both of Mongolian origin. A large number of anthropometric characteristics (about 50) were taken on each individual using a standardized technique. The group surveyed was divided into groups according to the BMI values recommended by WHO for Asia. General anthropometric characteristics and obesity-related indexes were compared between the overweight/obesity group and the control group. The genotyping for the polymorphic system of the fat mass and obesity-associated genes (T/A, rs9939609) was performed. The correlation between different genotypes and obesity-related anthropometric traits was analyzed. Results: Body mass, body mass index, waist circumference, hip circumference, waist-hip ratio, body fat percentage were higher in the overweight and obesity groups compared with controls. The frequencies of AA genotype and A allele in the obesity group were higher than those in the control group. The body weight, BMI, waist circumference, hip circumference, and waist-to-hip ratio in individuals with rs9939609 AA and AT genotypes were significantly higher than in those with TT genotype. Conclusion: Young men in Ulaanbaatar, Mongolia carrying the A allele accumulate more fat with the same BMI, mainly in the abdominal region, which indicates increased risks of developing diseases associated with central obesity.